Innovation of Non-Formal Education Platform Features in Indonesian Fashion - Juzma, Elma Khoiru; Murdowo, Djoko; Adriyanto, Andreas Rio (EduLine: Journal of Education and Learning Innovation, 2025)
Creating innovation to increase students' interest in improving soft skills and hard skills in various circles of society, so that they are able to create a new business in the fashion sector and improve the community's economy is the purpose of this research. Education is a process of changing people's attitudes, both individuals and groups, to improve knowledge and skills through learning, development and training both formally and non-formally. This study discusses the low public interest in non-formal education in Indonesia, especially non-formal education in the fashion sector. The research method used is the design thinking method to help the process of creating innovation which begins with conducting research on various types of products including websites and applications that will help fashion education. The results of the study are in the form of an innovation in talent/career channeling features, Project sharing and modules with complete content materials according to class level/level which are packaged in a low-fidelity prototype which has a low level of precision and does not yet describe the final product.